Difusión de los “mitos y leyendas” como herramienta para desarrollar el turismo cultural del cantón Babahoyo, provincia de los Ríos - Ortega Alarcón, Alex Eduardo (2018)
Cultural tourism is the source that allows us to investigate many cultural derivatives, it is the essence of our beginnings, it is the key to the knowledge of humanity, the objective of this research is to develop cultural tourism through the dissemination of myths and legends as a tool to publicize extraordinary events of myths and legends that are of utmost importance to clarify these historical accounts that had events long ago, myths and legends can be fictional or real, the important thing is that they are part of the cultural identity of a town and its inhabitants, cultural tourism also called Historical because of its importance in the life of the human being, cultural identity is the permanent hallmark of each town, ethnic group, which as time goes by incorporating their new lives customs that with the passage of time are formed in culture. Through the myths and legends and the good dissemination of them, it will be possible to maintain and preserve this culture to the current generations, so that they are the exponents of these events that will give the necessary value to the Babahoyense culture and increased the development of tourism. cultural benefit to the inhabitants of the communities improving the quality of life.